2020
DOI: 10.1007/s43032-019-00019-2
|View full text |Cite
|
Sign up to set email alerts
|

Metformin Promotes Anti-tumor Biomarkers in Human Endometrial Cancer Cells

Abstract: Metformin (MET) is increasingly implicated in reducing the incidence of multiple cancer types in patients with diabetes. However, similar effects of MET in non-diabetic women with endometrial cancer (EC) remain unknown. In a pilot study, obese non-diabetic women diagnosed with type 1, grade 1/2 EC, and consenting to participate were randomly assigned to receive MET or no MET (control (CON)) during the pre-surgical window between diagnosis and hysterectomy. Endometrial tumors obtained at surgery (MET, n = 4; CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 57 publications
1
18
0
Order By: Relevance
“…The in vivo relevance of PGR signaling as a MET target is supported by our previous study showing the induction of total PGR protein levels in the endometrial tumors of non-diabetic patients with EC following short-term pre-surgical MET treatment (13). The present study reports the novel finding that changes in glucose conditions modify the effects of MET on PGR signaling.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…The in vivo relevance of PGR signaling as a MET target is supported by our previous study showing the induction of total PGR protein levels in the endometrial tumors of non-diabetic patients with EC following short-term pre-surgical MET treatment (13). The present study reports the novel finding that changes in glucose conditions modify the effects of MET on PGR signaling.…”
Section: Discussionsupporting
confidence: 79%
“…The Ishikawa human endometrial epithelial carcinoma cell line (a gift from Dr Bruce Lessey, Greenville Health System; Prisma Health) was authenticated and propagated as previously described ( 13 ). Cells were initially grown in Minimal Essential Media (MEM; Gibco; Thermo Fisher Scientific, Inc.), supplemented with 10% (v/v) fetal bovine serum (FBS; Gibco; Thermo Fisher Scientific, Inc.) and containing phenol red and 1% antibiotic-antimycotic solution (Invitrogen; Thermo Fisher Scientific, Inc.) in a humidified incubator (5% CO 2 /95% air) at 37°C.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, the results of an in vitro study using ECC-1 and Ishikawa cells demonstrated that metformin reduced cell proliferation and increased AMPK activation in a dose-dependent manner, and indicated that the mTOR signaling pathway inhibition contributed to these effects (48). Metformin has been found to be functionally similar to an mTOR inhibitor, and the PTEN signaling pathway, which is tightly associated with the carcinogenesis of EC, may also be a target of metformin (49). Experiments in mice demonstrated a 50% reduction in the weight of EC xenografts following treatment with metformin, mediated via inhibition of the LKB1-AMPK-mTOR signaling pathway (50).…”
Section: Metformin Directly Inhibits the Development Of Ecmentioning
confidence: 99%